SCIENCE FICTION IN THE ISLAND OF DR. MOREAU AND THE TIME MACHINE - Abdulmon`em, Meryana Emad (Journal of Humanities & Social Sciences, 2018)
The present research paper is about two different novels, which are the Island of Doctor Moreau and the Time Machine, which are written by H.G.Wells; who is one of the most prominent writers in the 20th century. The main objective of this research paper is to explore the theme of science fiction and reveal the role of literature to express the power of science fiction, as the human beings can create and innovate, because they cannot do so if they are prisoners of their limited reality. As all people in the 20th century concentrate on scientific theories and struggles between classes, H.G.Wells reflects these two ideas according to his point of view in his works; the Time Machine and the Island of Doctor Moreau, using the power of science fiction to imagine other worlds that are not available in concentrate reality, predicting how the life will be and how to live within for the outside world past and future.